Pemanfaatan Teknologi Digital Dalam Pembelajaran Untuk Meningkatkan Literasi Digital Bagi Guru-Guru Di SD Muhammadiyah Purworejo - Anjarini, Titi; Primartadi, Aci; Agustina, Elsa; Risma, Nurlita (Pakis Journal Institute, 2024)
The development of technology today is very rapid, with the development of information technology and the internet, there are abundant digital information resources available. Based on the results of observations at SD Muhammadiyah Purworejo, several problems were found, namely 1) limited internet network while the infrastructure at the elementary school is very supportive of facilities such as computers, LCDs and adequate projector screens, in which case not all teachers or students have access to adequate devices such as computers, tablets, or smartphones needed to access Kahoot and Quizizz. 2) There are still teachers whose levels of competence vary from one another in mastering digital technology in learning, which in this case is the lack of mastery of the features in Kahoot and Quizizz which requires time and effort. 3) lack of training activities in making digital media. The objectives of this training activity include: 1) To improve teachers' digital literacy in mastering digital technology, 2) Train teachers to use interactive applications such as Khaoot and Quizizz, so that learning activities become more interesting and interactive, 3) Improve the quality of learning by creating more varied and more interesting teaching materials, 4) Improve evaluation skills presented with Khahoot and Quizizz. This research method was carried out with a qualitative approach, involving observation, interviews, and training analysis. The results of this training activity This training also proves that with mentoring and direct practice, teachers can easily integrate technology into learning, providing sustainable benefits for the education process. This training activity not only improves teachers' digital literacy, but also has a positive impact on the quality of student learning.